Catheter Ablation of Parahisian Premature Ventricular Complex - Kim, Jun (The Korean Society of Cardiology, 2011)
Catheter ablation is performed in selected patients with a symptomatic premature ventricular complex (PVC) or PVC-induced cardiomyopathy. Ablation of PVC from the His region has a high risk of inducing a complete atrioventricular block. Here we report successful catheter ablation of a parahisian PVC in a 63-year-old man.